Klausul Arbitrase Syariah Sebagai Dasar Penolakan Sengketa di Pengadilan Agama Pamekasan - Ach Saifullah (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2026)
This study aims to analyze the basis for the rejection of the dispute by the Pamekasan Religious Court due to the existence of a sharia arbitration clause in Decision Number 1321/Pdt.G/2017/P.A. Pmk. The problems studied in this study include the position of the sharia arbitration clause in sharia economic disputes, the absolute authority of the Religious Court and its limits, and the judge's legal considerations in rejecting the lawsuit. This study uses qualitative research methods with a normative juridical approach and a case approach. Data was obtained through literature studies by examining laws and regulations, court decisions, and relevant legal literature. The results of the study show that the sharia arbitration clause has binding force as a valid arbitration agreement, thus causing legal consequences in the form of transferring the dispute resolution forum from the Religious Court to the sharia arbitration institution. The absolute authority of the Religious Court in sharia economic disputes is not absolute if the parties have agreed on the sharia arbitration clause in the contract. The judge's legal considerations in the judgment under review show the application of the provisions of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution as well as the principle of pacta sunt servanda as the basis for rejecting the dispute. This study concludes that the rejection of the dispute provides legal certainty, but also requires an adequate understanding from the parties regarding the legal consequences of the sharia arbitration clause to ensure legal protection and substantive justice.